2013
DOI: 10.1016/j.phrp.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Multidrug-resistant Nonvaccine Serotypes in Pneumococcal Carriage of Healthy Korean Children Associated with the Low Coverage of the Seven-valent Pneumococcal Conjugate Vaccine

Abstract: ObjectivesOur previous longitudinal multicenter-based carriage study showed that the average carriage rate of Streptococcus pneumoniae was 16.8% in 582 healthy children attending kindergarten or elementary school in Seoul, Korea. We assessed serotype-specific prevalence and antimicrobial resistance among colonizing pneumococcal isolates from young children in the era of low use of the seven-valent pneumococcal conjugate vaccine (PCV7).MethodsSerotypes were determined by an agglutination test with specific anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Similar observations were reported in Norway and Colombia [29, 37]. Importantly, as in other studies (39, 40), most 19A strains in our study were resistant to three or more antibiotics.…”
Section: Discussionsupporting
confidence: 92%
“…Similar observations were reported in Norway and Colombia [29, 37]. Importantly, as in other studies (39, 40), most 19A strains in our study were resistant to three or more antibiotics.…”
Section: Discussionsupporting
confidence: 92%
“…Given that the most common drug resistant strains were included in 7-and 13-valent pneumococcal conjugate vaccines, drug resistant pneumococcal disease has been greatly reduced in areas with high vaccine uptake [18], while reductions in strain carriage also reduced secondary pneumonia cases among older adults [17]. However, recent studies from Canada and the United Kingdom demonstrated substantial increases in multidrug resistant non-vaccine serotypes in both colonizing and invasive strains since introducing PCV13, with similar findings for colonizing strains after introducing PCV7 in Korean children [19][20][21].…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
“…In addition, the introduction of PCV has resulted in a reduction in antimicrobial resistant pneumococci amongst circulating strains due to the inclusion of serotypes associated with high antibiotic resistance in the conjugate vaccine (14). However, non-vaccine-serotypes have emerged among both carriage and disease-causing isolates, and are increasingly associated with antimicrobial resistance (15,16). Increasing pneumococcal resistance to different classes of antibiotics, including beta-lactams, macrolides, tetracyclines, and cotrimoxazole, has compromised the effectiveness of antibiotics to treat pneumococcal infections (17).…”
Section: Introductionmentioning
confidence: 99%